INTERNALISASI NILAI-NILAI ISLAM DALAM PEMBENTUKAN KARAKTER: Analisis Psikologis dan Dampaknya Pada Perilaku Prososial - Muda, Ishak Ali; Lubis, M. Syukri Azwar (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2025)
This study explores the strategies and challenges in applying Islamic values to build the character of the young generation with noble character. Using the library research method, data was collected from various relevant academic literatures. The research findings show that the implementation of Islamic values can be done effectively through an integrated curriculum, daily activities, and the central role of teachers as behavioural models. The urgency of this implementation lies in its ability to strengthen students' moral and social foundations, which are much needed in the modern era. Nonetheless, there are some significant obstacles, including variations in students' backgrounds, limited time allocation in the curriculum, and the impact of the external environment. Synergy between educational institutions, parents and communities is needed to overcome these challenges and create a holistic educational environment.